SUPPORT TO YOUNG FARMERS THROUGH AGRICULTURAL POLICY MEASURES – THE EXPERIENCE OF THE EU AND SERBIA - Katarina Djuric; Boris Kuzman; Radivoj Prodanovic (Ekonomika Poljoprivrede (1979), 2019)
The purpose of this paper is to analyze agricultural policy measures aimed at young farmers and to compare the support system of the European Union and the Republic of Serbia. The dominant method in the research is the descriptive analysis. The comparative analysis method is used for investigating advantages and limitations of the support to young farmers in the EU and the Republic of Serbia. The unfavorable age structure of farmers represents the essential limitation for the sustainable development of agriculture and rural areas. In order to solve this problem, it is necessary to improve and strengthen agricultural policy measures of support to young farmers, which will lead to property increase, diversification of income and higher standards of living and consequently to the decision of young people to stay in the village and work in agriculture.